Prophylactic antiepileptic agents after head injury: a systematic review. Issue 1 (1st January 1998) - Schierhout, Gill; Roberts, Ian
Abstract : OBJECTIVE: To determine the effectiveness and safety of prophylactic antiepileptic agents in the management of acute traumatic head injury. METHODS: Systematic review of randomised controlled trials identified using MEDLINE, EMBASE, CINAHL, Dewent Biotechnology abstracts, and specialised databases of randomised controlled trials, by searching reference lists and contacting investigators. RESULTS: Ten eligible randomised controlled trials were identified, including 2036 patients. The pooled relative risk (RR) for early seizure prevention was 0.34 (95% confidence interval (95%CI) 0.21–0.54); based on this estimate, for every 100 patients treated, 10 would be kept seizure free in the first week. Seizure control in the acute phase was not accompanied by a reduction in mortality (RR=1.15; 95% CI 0.89–1.51), a reduction in death and neurological disability (RR=1.49; 95% CI 1.06–2.08 for carbamazepine and RR=0.96; 95% CI 0.72–1.26 for phenytoin) or a reduction in late seizures (pooled RR=1.28; 95% CI 0.90–1.81). The pooled relative risk for skin rashes was 1.57 (95% CI 0.90–2.75). CONCLUSIONS: Prophylactic antiepileptic drugs are effective in reducing early seizures, but there is no evidence that treatment with such drugs reduces the occurrence of late seizures, or has any effect on death and neurological disability. Insufficient evidence is available to establish the net benefit of prophylactic treatment at any time after injury.